Doktrin Penyalahgunaan Hak (abus des droit) - Salam, Syukron (Jurnal Hukum & Pembangunan, 2025)
The present article examines the emergence of the doctrine of abus de droit in France in the mid-twentieth century through an analysis of key judicial decisions and the debates that followed them. The study commences with an exposition of the manner in which the evolution of capitalism, concomitant with the escalating economic disparity and the propagation of societal challenges, has influenced the judicial approach to the abstract Roman-law tradition of absolute rights. In light of this, the article contends that the civil-law tradition exhibited a fundamental flaw in its conceptualisation of rights as absolute, thereby overlooking objections that were firmly rooted in considerations of social purpose and the social function of rights. The doctrine of abus de droit was developed to address situations in which a right-holder exercises an otherwise lawful right with malicious intent, or in a manner that causes unjustified harm to others. However, the doctrine remains contested. The question of whether the exercise of a right can constitute an abuse has been met with a divided response amongst jurists. On the one hand, there are those who reject the notion outright, while on the other hand, there are those who contend that the law of unlawful acts (responsabilité délictuelle), even when broadly interpreted, is insufficient to establish liability for abusive conduct. These disagreements ultimately gave rise to two competing views of the doctrine's legal foundation: one treats abus de droit as an extension of the concept of unlawful acts, while the other considers it a distinct doctrine that should be explicitly formulated in the civil code